WSe2 nanowires-based nanofluids for concentrating solar power. (January 2023) - Martínez-Merino, P.; Alcántara, R.; Navas, J.
Abstract: Tungsten selenide belongs to the family of inorganic compounds denominated transition metal dichalcogenides (TMDCs). There is emerging interest in these compounds in the field of optoelectronics, catalysis, sensing or energy storage, among others. Most works focus on the use of these materials in their 2D form but there is scarce research on the study of TMDCs nanomaterials with one-dimensional morphology. In this work, we explore the thermophysical properties of nanofluids based on 1D-WSe2 nanostructures with the aim of studying the feasibility of these nanofluids as heat transfer fluids in concentrating solar power plants. In this respect, nanofluids with a high heat transfer rate could increase the thermal efficiency of solar power plants, which would reduce the energy dependence on fossil fuels. Nanofluids of 0.02 wt%, 0.05 wt% and 0.10 wt% WSe2 concentrations have been prepared by the two-step method considering a thermal fluid used in solar power plants as the base fluid. The results of extinction coefficient evolution, ζ potential and particle size in suspension show a high colloidal stability over time of the prepared nanofluids mainly because of the high aspect ratio of the 1D-WSe2 nanomaterial. Additionally, the one-dimensionality and length of the synthesized nanowires favors the transport of heat in controlled directions, obtaining increases in thermal conductivity with respect to the base fluid of up to 16.8% in the highest concentration nanofluid. Improvements in isobaric specific heat of up to 15.7% and heat transfer of up to 20.8% compared to the base fluid have also been found. The results of this paper provide evidence that the presence of WSe2 nanowires induces increases in the thermal properties of the fluid commonly used in concentrating solar power plants without inducing agglomeration or sedimentation problems. Therefore, the nanofluids based on 1D-WSe2 nanostructures prepared in this work have a high potential to be used as heat transfer fluids in concentrating solar power plants based on parabolic trough collectors. Graphical abstract: Image 1 Highlights: WSe2 nanowires were successfully synthesized. Highly-stable nanofluids based on WSe2 nanowires were prepared. The one-dimensionality of NWs favors the heat transport in controlled directions. Thermal properties were improved with respect to the typical fluid in CSP plants. An enhancement of the heat transfer of up to 20.8% was found.